La dinámica familiar frente al embarazo en adolescentes ubicadas en el barrio Iguaraya del distrito de Riohacha
This research aimed to analyze family dynamics in the context of adolescent pregnancy in the Iguaraya neighborhood of the Riohacha district. The issue focuses on how adolescent pregnancy affects family relationships, causing significant changes in communication, roles, and household structure. The theoretical framework was based on studies of family dynamics and adolescent development theories. A mixed methodology was employed, combining qualitative and quantitative techniques. The study involved a sample of seven pregnant adolescents aged 15 to 18 residing in the Iguaraya neighborhood